Separating top-down and bottom-up cueing of attention from response inhibition in utilization behavior. - Balani, AB; Soto, D; Humphreys, G (2012)
A single case study of a patient (FK) with utilization disorder following bilateral damage to medial frontal and anterior temporal cortices is reported. FK had to localize a search target following presentation of an earlier verbal or visual cue. Search was strongly affected by semantic/visual associations between the cue and search items. Although FK was unable to name the hue of an incongruent Stroop word, his attention was drawn to a color in the display matching the hue of the cue word. FK's ability to inhibit a response activated by the cueing of attention was impaired. There is dissociation between top-down attention cueing and response inhibition.